2011
DOI: 10.1175/2010jcli3775.1
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Inherent Predictability of Arctic Sea Ice in a GCM Ensemble and Observations

Abstract: The temporal characteristics of Arctic sea ice extent and area are analyzed in terms of their lagged correlation in observations and a GCM ensemble. Observations and model output generally match, exhibiting a red-noise spectrum, where significant correlation (or memory) is lost within 2–5 months. September sea ice extent is significantly correlated with extent of the previous August and July, and thus these months show a predictive skill of the summer minimum extent. Beyond this initial loss of memory, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
233
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(275 citation statements)
references
References 38 publications
39
233
3
Order By: Relevance
“…Relatively little skill remains both for CanSIPS (Figure 1a) and CFSv2 (Figure 1b) after lead two (the third forecast month), although there is some evidence for longer-lead skill, primarily for target months in late fall (mainly for CFSv2) and winter (for both systems). This apparently corresponds to an observed tendency for detrended cold-season anomalies in ice area and extent to be correlated from one year to the next, possibly as a result of slowly varying ocean thermal influences in regions of winter ice cover as discussed by Blanchard-Wrigglesworth et al [2011a].…”
Section: Resultssupporting
confidence: 71%
“…Relatively little skill remains both for CanSIPS (Figure 1a) and CFSv2 (Figure 1b) after lead two (the third forecast month), although there is some evidence for longer-lead skill, primarily for target months in late fall (mainly for CFSv2) and winter (for both systems). This apparently corresponds to an observed tendency for detrended cold-season anomalies in ice area and extent to be correlated from one year to the next, possibly as a result of slowly varying ocean thermal influences in regions of winter ice cover as discussed by Blanchard-Wrigglesworth et al [2011a].…”
Section: Resultssupporting
confidence: 71%
“…The observed detrended Arctic sea ice extent, based on ensemble hindcasts can be predicted up to 2-7 and 5-11 months ahead for summer and winter, respectively (e.g., Chevallier et al, 2013;Sigmond et al, 2013;Wang et al, 2013;Msadek et al, 2014;Peterson et al, 2015;Guemas et al, 2016;Sigmond et al, 2016). In these ensemble hindcasts, it is found that ice thickness and surface or subsurface water temperatures are closely related to the prediction skill, as suggested by idealised or perfect-model experiments with climate models (e.g., Blanchard-Wrigglesworth et al, 2011b;Chevallier and Salas y Mélia, 2012;Day et al, 2014a).…”
Section: Introductionmentioning
confidence: 86%
“…Blanchard-Wrigglesworth et al (2011) analyse the lagged correlation of the Arctic sea ice in observations and a GCM ensemble. They showed a persistence of total sea ice area anomalies for the 1-5-month time scale, longer in winter and summer months and shorter in spring and fall months.…”
Section: Discussionmentioning
confidence: 99%